Waqf Land Disputes and Alternative Settlements - Faisal Faisal (RIRAI Publisher, 2021)
The system of Waqf management is still not as expected because many land dispute problems that arise in the midst of society are caused by factors that hinder the delivery of Waqf intentions from a representative. The issue of Waqf disputes is often brought to the path of litigation (court) so that alternative channels are needed in finding a resolution. The research method used is the method of juridical law research normative with the approach of legislation. The purpose of this research is to prioritize non-litigation pathways first to resolve Waqf disputes. The results showed that the factors that cause the non-implementation of Waqf lies in administrative problems when trying to make a deed of Waqf land pledge caused by disapproval by the heirs of the representative to the management of Waqf by nadzir who lack integrity and responsiveness. Recommendations on the issue, Waqf disputes should first put forward a non-Litigation line, because the Litigation line as a last resort to find a place to resolve land disputes.